Vegetation (Scotland), 1973 - Countryside Commission for Scotland (1988)
Abstract copyright UK Data Service and data collection copyright owner. These data record the classification (12 categories) of the vegetation cover of each 5 km square in Scotland. Main Topics: Variables Number of types of vegetation per 5 km square, including Arctic-Alpine vegetation; sub-Alpine moors; peat moors, mosses and bogs; wet grass moors; dry grass moors; heather moors; acid grasslands; sand dunes and links, cliff tops; saltings; improved land; chief woodland areas; principal urban areas.